O problema de Dirichlet para a EDP da curvatura média constante em variedades de curvatura de Ricci não negativa - Müller, Nícolas Moro (2018)
In this work we study the Dirichlet problem for the constant mean curvature equation in bounded, mean convex and C2; - domains contained in a complete Riemannian manifold. We show an existence and uniqueness result for the case where the Ricci curvature of the manifold is non-negative and the boundary data is zero.